“Pathological Physiology of Heart Failure” (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Heart failure is an epidemic disease which affects about 1% to 2% of the population worldwide. Both, the etiology and phenotype of heart failure differ largely. Following a cardiac injury (e.g., myocardial infarction, increased preload or afterload) cellular, structural and neurohumoral modulations occur that affect the phenotype being present. These processes influence the cell function among intra- as well as intercellular behavior. In consequence, activation of the sympathoadrenergic and renin-angiotensin-aldosterone-system takes place leading to adaptive mechanisms, which are accompanied by volume overload, tachycardia, dyspnoea and further deterioration of the cellular function (vicious circle). There exists no heart failure specific clinical sign; the clinical symptomatic shows progressive deterioration acutely or chronically. As a measure of cellular dysfunction, the level of neurohormones (norepinephrine) and natriuretic peptides (e.g., NT-pro BNP) increase. For the diagnosis of heart failure, noninvasive (echocardiography, NMR, NT-proBNP) and invasive (heart catheterization, biopsy) diagnostic procedures are implemented. Modulation of the activated systems by ß-blocker, ACE-inhibitors and ARNI improve outcome and symptoms in heart failure patients with left ventricular dysfunction. Interventional and surgical therapy options may be performed as well. The understanding of the underlying pathophysiology of heart failure is essential to initiate the adequate therapeutic option individually for each patient. Furthermore, prevention of cardiovascular risk factors is essential to lower the risk of heart failure.